Multiloop controller and reference generator for a dynamic voltage restorer implementation - Marafão, Fernando Pinhabel [UNESP]; Colón, D. [UNESP]; Jardini, J. A.; Komatsu, W.; Matakas, L.; Galassi, M.; Ahn, S. U.; Bormio, E.; Camargo, J. C.; Monteiro, T.; Oliveira, M. A. (Institute of Electrical and Electronics Engineers (IEEE), 2008)
This paper deals with the design and analysis of a Dynamic Voltage Restorer output voltage control. Such control is based on a multiloop strategy, with an inner current PID regulator and an outer P+Resonant voltage controller. The inner regulator is applied on the output inductor current. It will be also demonstrated how the load current behavior may influence in the DVR output voltage, which justifies the need for the resonant controller. Additionally, it will be discussed the application of a modified algorithm for the identification of the DVR voltage references, which is based on a previously presented positive sequence detector. Since the studied three-phase DVR is assumed to be based on three identical H-bridge converters, all the analysis and design procedures were realized by means of single-phase equivalent circuits. The discussions and conclusions are supported by theoretical calculations, nonlinear simulations and some experimental results. ©2008 IEEE.
Keywords: Dynamic voltage restorer; Feedback control systems; Positive sequence; Power electronics converters; Resonant controller; Adaptive control systems; Control systems; Electric potential; Equivalent circuits; Feedback; Feedback control; Identification (control systems); Power electronics; Power quality; Turbulent flow; Videodisks; Voltage control; Voltage regulators; Analysis and designs; Design and analyses; H bridges; Load currents; Modified algorithms; Multiloop controllers; Nonlinear simulations; Output inductors; Output voltages; Pid regulators; Reference generators; Theoretical calculations; Voltage controllers; Voltage references; Electric control equipment